Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--16460
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Of Peerwise As An Educational Tool For Bioengineers

Abstract: Her interests include identifying novel strategies to integrate teaching and research and enhancing the recruitment and retention of underrepresented populations in engineering. Dr. Micou is the program director of an NSF-sponsored Research Experience for Undergraduates (REU) program in Regenerative Medicine, Multi-Scale Bioengineering, and Systems Biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, while each of these individual activities has the potential to enhance academic achievement, studies have shown that it is through engaging across a range of PeerWise activities that students can best improve their understanding and academic performance (McQueen, Shields, Finnegan, Higham, & Simmen, ). Previous studies of students’ overall use of PeerWise (see for example Casey et al ., ; Denny, Hamer, Luxton‐Reilly, & Purchase, ; Denny, Luxton‐Reilly, Hamer, & Purchase, ; Denny, Simon, & Micou, ; Hardy et al , ) have used a “Multiple Measure” (MM); a combined measure of activities that can be said to represent the aggregate of the “work done” by a student using the system. However, this measure is largely based on the quantity of student contributions (number of questions written and answered, number of days active, length of comments), which does not necessarily reflect the quality.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Interestingly, while each of these individual activities has the potential to enhance academic achievement, studies have shown that it is through engaging across a range of PeerWise activities that students can best improve their understanding and academic performance (McQueen, Shields, Finnegan, Higham, & Simmen, ). Previous studies of students’ overall use of PeerWise (see for example Casey et al ., ; Denny, Hamer, Luxton‐Reilly, & Purchase, ; Denny, Luxton‐Reilly, Hamer, & Purchase, ; Denny, Simon, & Micou, ; Hardy et al , ) have used a “Multiple Measure” (MM); a combined measure of activities that can be said to represent the aggregate of the “work done” by a student using the system. However, this measure is largely based on the quantity of student contributions (number of questions written and answered, number of days active, length of comments), which does not necessarily reflect the quality.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…and give comments to peers than is asked of them as a minimum requirement, suggesting high levels of interest and engagement in the course material. Alongside these outcomes, a further finding has indicated that there is a correlation with higher summative assessment scores and students with higher levels of scores (Bates et al, 2012;Casey et al, 2014;Denny et al, 2010;Feeley & Parris, 2012).…”
Section: Online Tools For the Development Of Higher Order Thinkingmentioning
confidence: 97%